Valuation Approach for Assessing Efficiency of Agricultural Land Use - Kovalyshyn, Oleksandra; Buśko, Małgorzata; Tretiak, Nataliia; Kovalyshyn, Oleh; Pendzey, Lubov; Tretiak, Roman; Muzyka, Nataliia (Geomatics and Environmental Engineering, 2025)
This article is devoted to studying the peculiarities of applying the valuation approach toward assessing the efficiency of agricultural land use. In particular, it was determined that the main link of the valuation approach was the value of the land use. Value is the basis of quantitative correlation under the equivalent exchange; the value of land use can be determined by applying three common approaches: comparison, cost, and income. The authors of the research present a methodology for assessing the value of the right to manage agricultural land use and its efficiency. The work supplies the calculated book value of land use under the actual status of agricultural lands in Ukraine according to the average indicators (in the present research, this was the period of 2017–2021) and the economic market value of land use while considering innovative investments in land improvement that are focused on establishing the more effective use of agricultural lands. It is stated that the valuation approach toward assessing the efficiency of agricultural land use can be used to specify the value of the right to manage land use in the amount of its general value as well as assess its efficiency. The suggested algorithm and statistical indicators were used to calculate the right and efficiency of agricultural land use management for all categories of farms and, particularly, in terms of agricultural enterprises of the different forms of economic activity.